Penggunaan Media Permainan Monopoli untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas V SDN 7 Cakranegara - Julkifliati, Julkifliati; Muslehudin; Zain, Irawan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study is a Classroom Action Research (CAR) that aims to describe the use of game-based learning media, determine the improvement of students’ learning motivation, assess their activeness in learning activities, and identify the improvement of learning outcomes among fifth-grade students at SDN 7 Cakranegara. The research was conducted in two cycles using observation, questionnaires, and interviews as data collection methods, and the data were analyzed quantitatively using descriptive analysis. The results showed that the use of the Monopoly game as a learning medium significantly increased students’ learning motivation. Students’ average motivation score increased from 61.2% (Moderate) in the pre-cycle to 74.8% (Good) in Cycle I, and further to 87.5% (Very Good) in Cycle II. This improvement was also reflected in students’ activeness and learning outcomes. The activeness score increased from 54.5% (Low) in the pre-cycle to 73.7% (Good) in Cycle I, and reached 88.1% (Very Good) in Cycle II. Similarly, the average test score improved from 65.4 with a mastery percentage of 52.0% in the pre-cycle to 75.8 with 76.4% mastery in Cycle I, and finally to 85.2 with 92.3% mastery in Cycle II. These findings indicate that Monopoly-based learning media is effective in enhancing students’ motivation, activeness, and learning achievement in elementary school.